Development of a Facial Recognition-based Attendance System using Binary Patterns Histograms Method and Telegram Bot Notification - Qois Amin Fauzan; Aris Budianto; Cucuk Wawan Budiyanto (Pendidikan Teknik Informatika dan Komputer, Universitas Sebelas Maret, 2022)
In carrying out attendance activities, most schools still use the manual attendance method, which utilizes the attendance book as a medium. However, the presence of the manual still causes some problems that arise when using this method. With the aim of this study, a